Ultrasound-guided transversus abdominis block vs wound infiltration in patients undergoing open appendectomies - Bayındır, Serpil; Özcan, Sibel; Koçyiğit, Fatma; Bozan, Mehmet Bugra (My University, 2018)
The aim of this study was to compare USG-guided Transversus Abdominis Plan Block (TAP) and wound infiltration in terms of intraoperative parameters, postoperative complications, VAS scores, analgesic requirement time in the patients undergoing open appendectomy. A total of forty patients, aged 18-65 years, ASA physical status I or II scheduled to undergo open appendectomy, were enrolled in this retrospective study and allocated to two groups. We reviewed the procedures that was experienced in 2014 retrospectively. Patients were allocated into two equal groups: Transversus Abdominis Plan Block (TAP group) (n=20) group and wound infiltration (WD group) (n=20) group. The patients demographic datas such as intraoperative hearth rate (HR), noninvasive blood pressure (NBP), duration of anesthesia, postoperative Visuel Analog Scala (VAS) values, complications (nausea, vomiting, somnolence, wound infection, ichting), duration of analgesic requirement were recorded retrospectively. The data were compared using t-test and chi-square test within the groups, p values < 0.05 were considered significant. Demographic datas such age, sex, weight, lenght and ASA status were similar in both groups. The duration of anesthesia (min) was significantly higher in Group TAP (49 ± 12,2 min) compared with Group WD (32,75 ± 10,06 min) (p=0.001). Intraoperative opioid consumption (mcg) was significantly shorter in Group TAP group. There was statistically significant difference between the two groups as regards the first time of analgesic requirement (Group TAP 24,74 ± 7,77 h, Group WD 3,5 ± 3,52 h). HR values were compared between the groups, it was no significiant difference found expect HR-20, HR-25 and HR-30. it was lower in Group TAP. We didn’t find significant difference between groups at all hours for postoperative complications. VAS pain scores were lower in Group at rest and on couching at PACU, postoperative first, second and third hours (p<0.05). Wound infiltration and TAP block can perform as a part of the multimodal analgesia of the patients who undergoing open appendectomy. TAP block application prolongs the duration of anesthesia as well as reduces intraoperative analgesic requirement and initial postoperative analgesic requirement period. The fact that VAS scores were lower in the TAP block group showed that the multimodal analgesia regimen could be applied as an effective component.
Keywords: Tıbbi Araştırmalar Deneysel; Androloji; Cerrahi